The Tragedy of Clientelism: Opting Children Out - Lucas Ronconi; Rodrigo Zarazaga (Institute of Labor Economics (IZA), 2017)
Governments in new democracies launch social policies with the purported goal of alleviating the effects of poverty among the most vulnerable households, usually low income families with children. However, this goal is can be thwarted by the clientelistic distribution of social policies' benefits because politicians seek to maximize political support and children do not vote. Based on the main Argentine household survey and on personal interviews with 120 brokers, this paper shows that brokers collect information on family size and age composition and allocate temporary public works programs that are in excess demand discriminating against families with children not old enough to vote.
Keywords: K40; H53; I38; 330; clientelism; household; discrimination; social policy; Latin America; Argentina